CHANGED AREAS AND ECONOMIC ASPECTS OF ECOLOGICAL RESTORATION UNDER THE OPTICS OF THE ABC SYSTEM IN ANTIMARY STATE FOREST - Júnior, Raco Tanomaru; Vieira, Gil; Silva, Zenobio Abel Gouvêa Perelli da Gama e (Floresta, 2023)
This paper addresses ecological restoration in a Conservation Unit - CU, in the Amazon. Its objective was to generate information about the altered areas and possible ecological restoration techniques that can be used in the Antimary State Forest (ASF) to contribute to the CU management plan. In specific terms, this study aimed to: (1) identify and quantify the types of environmental change at ASF; (2) recommend ecological restoration methods and (3) quantify and analyze the costs of ecological restoration, considering the Activity Based Costing – ABC method. To this end, technical visits were made to the altered areas and experimental plots were implanted. The results generated indicate that the environmental changes in the ASF account for 5.5% of the UC area and are pastures in use or abandoned and abandoned agricultural areas. The recommended ecological restoration methods were to conduct assisted natural regeneration with or without planting enrichment seedlings and suggested ecological nucleation were of a low technological degree and easy to obtain inputs. The cost for the method of conducting assisted natural regeneration without enrichment was B 38,538.60/ha, of B 20,592.28/ha for the method of conducting assisted natural regeneration with enrichment planting and B 40,405.48/ha for the nucleation method with the costs of the techniques ranging from B 1,791.8/ha to B 8,224.84/ha. The isolation activity of the area was the mostly costly in all the ecological restoration methods studied.